ANALYSIS OF THE IMPLEMENTATION OF SHARIAH MARKETING VALUE IN LONTONG UMKM VILLAGE SURABAYA CITY - Shinta Nur Alifia; Rudi Hermawan (Jurnal Ekonomi, 2023)
MSME (Micro, Small and Medium Enterprises) is the main occupation in Lontong Village, Kupang Krajan Village, Surabaya City. The resulting product is rice cake, which is sold through online and offline marketing. This study aims to determine the application of shariah marketing values ​​to the MSME (Micro, Small and Medium Enterprises). This research was conducted using a qualitative descriptive method. Primary data sources were obtained through interviews with sellers. Secondary data is the people in Kampung Lontong Surabaya. Based on the research results, the sellers in Lontong Subdistrict, Surabaya City, have applied the shariah principles of marketing value through the values ​​of Use A Spiritual Brand Character (Brand), Services Should Have the Ability to Transform (Service), Practice A Reliable Business Process (Process). With the application of Shariah Marketing Values ​​for MSME Lontong (Micro, Small and Medium Enterprises) in the Kupang Krajan Village, Surabaya City, the quality, cleanliness and halalness of the products they sell are guaranteed, they can increase sales through online and offline marketing, the products they sell will continue to grow. Grow so that the profits you get will be even more significant, and also, the demand for this lontong product will increase so that the sellers can be better known in the community.